Charge breeding at GANIL: Improvements, results, and comparison with the other facilities - Maunoury, Laurent; Dubois, Mickael; Delahaye, Pierre; Annaluru, Arun; Bajeat, Olivier; Frigot, Romain; Hormigos, Stéphane; Jacquot, Bertrand; Jardin, Pascal; Osmond, Benoit; Predrag, Ujic; Retailleau, Blaise-Mael; et al. (Review of scientific instruments, 2020)
The 1+/n+ method, based on an ECRIS charge breeder (CB) originally developed at the LPSC laboratory, is now implemented at GANIL for the production of Radioactive Ion Beams (RIBs). Prior to its installation in the middle of the low energy beam line of the SPIRAL1 facility, the 1+/n+ system CB has been modified based on the experiments performed on the CARIBU Facility at Argone National Laboratory. Later, it has been tested at the 1+/n+ LPSC test bench to validate its operation performances. Charge breeding efficiencies as well as charge breeding times have been measured for noble gases and alkali elements. The commissioning phase started at GANIL in the second half-year of 2017. It consisted of a stepwise process to test the upgrade of the SPIRAL1 facility from simple validation [operation of Charge Breeder (CB) as a stand-alone source] up to the production of the first 1+/n+ RIB. Thus, this year, a 38mK/38K RIB has been successfully delivered to a physics experiment over a period of 1 week. The yields on the physics target were in the range of ∼2–4 × 106 pps at 9 MeV/u. The target ion source system (TISS) was made of a FEBIAD ion source connected to a hot graphite target. This is the first time a RIB is accelerated with a cyclotron with the 1+/n+ method. Moreover, a production test with the FEBIAD TISS has confirmed the yields measured previously, which validates the extension of the GANIL/SPIRAL1 catalog for a number of isotopes. In parallel, R&D is being performed on new TISSs (e.g., a fast release one, using surface ionization source). Targets are also a subject of ongoing R&D for yield and release time optimization. This contribution will present the new acceleration scheme of the SPIRAL1 facility, which largely extends the palette of RIBs available for nuclear physicists. It will be compared to the ones used at similar ISOL facilities. This facility is more than a simple ISOL facility, and an overview of the new opportunities offered by the upgraded installation will be also discussed.